Teknologi Pendidikan dan Transformasi Digital di Masa Pandemi COVID-19 - Novianti Indah Putri; Yudi Herdiana; Zen Munawar; Rita Komalasari (STMIK IKMI Cirebon, 2021)
Technology has an important role in controlling the crisis due to the impact of COVID-19. This research aims to determine the right technology and digital transformation that can be applied during the COVID-19 pandemic. With the pandemic, the door to digital transformation has opened, especially in the field of education. This research conducts a study of digital transformation due to the COVID-19 pandemic in the world of education with the aim of equipping them with important skills and competencies. With technology and digital transformation, it is hoped that it can generate interest in learning. In this study, a learning method is given based on the use of technology used during habitual adaptation. In addition, challenges are presented due to the current situation and recommendations for implementation and best practices. It has been found that the methods and techniques used have been very helpful and have increased student learning and enthusiasm during this difficult time